Fermentation of Banana Stem and Indigofera sp. Leaves Using MA-11 with Different Fermentation Durations on Nutritional Quality - Herlina, Febriana Puja; Mulyono, Ali Mursyid Wahyu; Husein, Muhammad (Jurnal Biologi Tropis, 2026)
Banana stems are an abundant agricultural by-product; however, their utilization as animal feed remains limited due to their high fiber and low crude protein contents. Improving their nutritional quality can be achieved through fermentation combined with the addition of protein sources and bioactivators. This study aimed to evaluate the effect of fermentation duration on the nutritional quality of a mixture of banana stems and Indigofera sp. leaves fermented using Microbacter Alfaafa (MA-11). The experiment was conducted for 12 days using a Completely Randomized Design (CRD) with three fermentation periods: 0 days (P0), 6 days (P1), and 12 days (P2), each with four replications. The observed parameters included crude protein, crude fiber, and dry matter biomass weight. Data were analyzed using analysis of variance (ANOVA), followed by Duncan’s Multiple Range Test at a 5% significance level. The results indicated that fermentation duration had a significant effect (P<0.05) on crude protein content, with the 12-day treatment producing the highest value (15.14%). In contrast, fermentation duration had no significant effect (P>0.05) on crude fiber content and dry matter biomass weight. In conclusion, 12 days of fermentation with MA-11 increased crude protein content but was not effective in significantly reducing crude fiber and dry matter biomass weight.